Komposisi Kimia dan Kualitas Fisik Daging Ayam Broiler Dimarinasi dengan Pasta Lengkuas pada Lama Penyimpanan Berbeda - Nuraini, Nuraini; Tasse, A. M.; Hafid, H.; Toba, R. D. S. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2018)
The aim of this study is to know the chemical composition and physical qualities breast meat broiler which is marinated in 20% galangal juice. The method used completely randomized design with stroge period, Treatments O hour (To), 3 hours (T1), 6 hours (T2), and 8 hours (T3) and four replications. Each treatment used breast meat broiler (BMB) 100 grams. Variables included chemical composition (moisture and crude protein %) and physical quality (cooking loss). The data analysis used analysis of Variance (ANOVA) and Tukey’s test The results that stroge period 9 hours (T3) has significant effect of cooking loss percentage but does not have significant effect of moisture content and crude protein content. The conclusion that storage period longer can increase cooking loss percentage and cannot change Chemical composition breast meat broiler marinated with galangal juice.